Qur'an and Arabic Camp: (Bridging The Gap Between Vocabulary Acquisition and Writing Proficiency in Arabic Language Learning: an Interactive Approach) - Rozaanah Rozaanah; Mardhatillah; Riri Maharani Munthe; Siti Khaila Murdy; Shiba Salsabila; Tika Rahmadani (Al-Arkhabiil)
This community service activity addresses the gap between vocabulary acquisition and writing proficiency in Arabic language learning among students at Madrasah Ar-Rabbaniyyah Darul Ikhlas Lilbanat, Malacca, Malaysia. Employing a Participatory Action Research (PAR) approach, this study identified key challenges in Arabic language learning and implemented innovative strategies to overcome them. The findings indicate that using interactive methods, visual materials, and graduated learning approaches effectively enhanced student motivation and comprehension. However, resource and time constraints remain significant challenges. This research highlights the importance of a holistic and contextual approach to Arabic language instruction within Islamic educational institutions, considering linguistic, pedagogical, and socio-cultural factors. The implications of this study encompass the need for appropriate learning material development, continuous teacher training, and technology integration in Arabic language education.